Pro Windows PowerShell - Deshev, Hristo; SpringerLink (Online service) (Berkeley, CA : Apress, Inc., 2008)
A guide to using Windows PowerShell to script Windows administrative tasks and control Windows from the command line.
Includes index.
Keywords: Microsoft Windows (Computer file); Operating systems (Computers); Computer Science; Programming Techniques